Cancer Immunoediting by Innate Lymphoid Cells. Issue 5 (May 2019) - Wagner, Marek; Koyasu, Shigeo
Abstract : The immune system plays a dual role in cancer. It conveys protective immunity but also facilitates malignant progression, either by sculpting tumor immunogenicity or by creating a microenvironment that can stimulate tumor outgrowth or aid in a subsequent metastatic cascade. Innate lymphoid cells (ILCs) embody this functional heterogeneity, although the nature of their responses in cancer has only recently begun to be unveiled. We provide an overview of recent insights into the role of ILCs in cancer. We also discuss how ILCs fit into the conceptual framework of cancer immunoediting, which integrates the dual role of the immune system in carcinogenesis. A broader understanding of their relevance in cancer is essential towards the design of successful therapeutic strategies. Highlights: ILCs have been implicated in both tumor-suppressing and tumor-promoting activities. The possibility to enhance and/or reorient their tumor-suppressing and/or tumor-promoting activities, respectively, provides an opportunity to design putative successful therapeutic approaches. Insights into how cancer cells regulate ILC function represent an important area of unfulfilled need towards the design of therapeutic strategies. An improved understanding of the biology of ILCs could help in the management of immunotherapy-related side effects arising from treatments, including those stemming from immune checkpoint blockade therapy.